A study of recreation interaction in the city of Kota Kinabalu - Kaede Chan Lip Chung; Andy Russel Mojiol (Faculty of Science and Natural Resources, 2021)
The green space is crucial for a human to promote health and enjoyment physically or mentally. However, recreation interaction is intangible, and it is difficult to measure in terms of the standardized framework due to personal preference changes. The focus of this paper is to study the relationship between census and recreation interaction in Kota Kinabalu. The questionnaire survey was conducted with a double selection of samples in Kota Kinabalu to collect 152 respondents' perceptions to study the recreation interaction. The finding of this paper is the race variable is the only variable that had a relationship with recreation interaction. Further, race is the factor that influences the change of preference in the experiment, and further research is needed to justify their relationship.